Twenty-Year Experience of a Single Referral Center on Pediatric Familial Mediterranean Fever: What Has Changed Over the Last Decade?. Issue 1 (January 2021) - Kisla Ekinci, Rabia Miray; Balci, Sibel; Dogruel, Dilek; Altintas, Derya Ufuk; Yilmaz, Mustafa
Abstract : Background/Objective: Familial Mediterranean fever (FMF) is the most common autoinflammatory disease and is characterized by recurrent fever and serositis episodes. We aimed to share our 20-year FMF experience, clarify a phenotype-genotype correlation, and compare the characteristics and outcomes of pediatric FMF patients over the last 2 decades in this study. Methods: This medical record review study included 714 pediatric FMF patients (340 females, 374 males), diagnosed by Tel Hashomer diagnostic criteria between January 2009 and January 2019 and followed up in our department. Demographic and disease characteristics, obtained from medical records of the patients, were compared between patients with M694V homozygosity and other genotypes and showed whether they were diagnosed before (n = 137) or after January 2010 (n = 577). χ 2, Student t, and Mann-Whitney U tests were used to compare categorical and continuous variables between these groups. Results: The most common symptoms were abdominal pain (92%), fever (89.5%), and arthralgia (64.5%). Mean ages at symptom onset and diagnosis were 5.16 ± 3.73 and 7.71 ± 3.87 years, respectively. M694V homozygosity was recorded in 111 patients (15.5%). Fever, arthralgia, arthritis, myalgia, erysipela-like erythema, colchicine resistance, and subclinical inflammation were more frequent, and mean disease severity score was higher in patients with M694V homozygosity. Fever, chest pain, and proteinuria were statistically more frequent in patients diagnosed before January 2010. Although M694V homozygosity rate was similar, patients diagnosed in the last decade had lower mean disease severity score. Conclusions: With this study, we speculate that although genotype and delay in diagnosis were similar, patients diagnosed in the last decade have a milder disease severity.